BUDDHIST MORAL EDUCATION FOR POSITIVE BEHAVIORAL CHANGE OF BUDDHIST STUDENTS - Utari, Meisi; Widiyono, Widiyono; Kiryono, Kiryono (Jurnal Pencerahan, 2023)
This study aims to determine the behavioral conditions of Buddhist students, the effect of Buddhist moral education, and the impact of Buddhist moral education on behavioral changes of Buddhist students at SDN Sumogawe 03. The research uses qualitative descriptive methods. The research data are collected by interview, observation, and documentation. The validity of the data was tested by persistence, triangulating, and member checking. The Data analysis is based on the Miles & Huberman model which consisted of data collection, data reduction, data presentation, drawing conclusions, and verification. The results of this study show that the behavioral conditions of Buddhist students at SDN Sumogawe 03 are classified into two, namely good behavior and bad behavior. The effect of Buddhist moral education on Buddhist students at SDN Sumogawe 03 is the occurrence of changes in students’ behavior in accordance with the rules of morality in the Buddhist Pañcasīla. Students who initially behave badly, such as killing, lying, and stealing, are able to change their behavior for the better. Changes in students’ behavior have an impact on students themselves and others. The impact of the behavioral change on students is that students can gain peace, gain the trust of others, foster self-confidence, discipline, and self-reliance. The impact of changes in the students’ behavior on other people which is seed is that other living beings can live without fear, other creatures can live in peace, and other people can have confidence in the students.